5 PRINCIPLES OF STUDENTS’ DEVELOPMENT OF ENGLISH SPEAKING - Ramazonov, Shohruh Nusratillo o‘g‘li; Ramazonov, Shohruh Nusratillo o‘g‘li (Educational Research in Universal Sciences, 2023)
The book starts off with explaining the 5 evidence-based principles of language development and acquisition. Andrea begins the book with these principles to lay the foundation for the strategies. They saw her as a scholar practitioner grounded in theory yet with established connections to educators in the field who are working diligently to grow students’ language and literacy skills.